The Identity of France / History and Environment Volume I - Braudel Fernand (Fontana Press, 1989)
Braudel sheds light on every aspect of France, from every conceivable angle. Introduction to the Identity of France, History and Environment, The Diversity of France, The Pattern of settlement: Villages and Bourges and Towns, Explaining the System: The Bourg, Explaining the System: The Towns, was France Invented by Its Geography?, The Frontier: A Crucial Test, History and Environment: A Few Last Words, Notes, Glossary, Index.